The expectation effect : how your mindset can change your world - Robson, David (Science journalist) (Henry Holt and Company, 2022)
"What you believe can make it so. A journey through the cutting-edge science of how our mindset shapes every facet of our lives, revealing how your brain holds the keys to unlocking a better you"--